REVIEW OF INNOVATIONS AND PROSPECTS FOR THE DEVELOPMENT OF THE BUSINESS ACCOUNTING AND TAXATION SYSTEM - SKRYPNYK, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article discusses the innovations and prospects for the development of the business accounting and taxation system in the modern economy. Considerable attention is paid to the process of implementing digital technologies operating in the European Union as the main example for Ukraine, which create an effective accounting and taxation system. The article covers the aspects of globalization and integration that affect Ukrainian business, as well as global trends and innovations that Ukraine can adopt. Ukraine's approach to harmonizing the tax system and implementing European financial reporting standards is important. This will make it possible to introduce a system of transparency and stability of financial flows, which is important for investors. The article discusses legislative aspects and innovations in taxation, such as the introduction of a digital services tax and environmental taxes. The principles of the business accounting and taxation system are investigated. The role of Ukraine in stimulating innovations in accounting and taxation is highlighted separately, and examples of successful initiatives by governments of different countries aimed at supporting small and medium-sized businesses through tax incentives and financial assistance programs are analyzed. Considerable attention is paid to cybersecurity issues in the context of digitalization of accounting and tax systems. The main threats and risks associated with the use of information technology are identified and approaches to minimizing them are proposed. The role of blockchain technologies in ensuring the security and transparency of financial transactions is outlined. The article concludes with forecasted trends in the development of the accounting and taxation system in the future. The author concludes that further introduction of innovations and technologies will be a key factor in improving the efficiency of business processes. The author emphasizes the need for continuous adaptation to new challenges and active participation of all stakeholders in the process of reforming the accounting and taxation system. It is recommended to introduce European standards to improve the efficiency and reliability of the business accounting and taxation system, which will contribute to its stable development and compliance with legal requirements.
Keywords: accounting system; business taxation; economic growth; tax procedures; financial flows; innovative approaches